Audit of radiology communication systems for critical, urgent, and unexpected significant findings. Issue 3 (March 2016) - Duncan, K.A.; Drinkwater, K.J.; Dugar, N.; Howlett, D.C.
Abstract : Aim: To determine the compliance of UK radiology departments and trusts/healthcare organisations with National Patient Safety Agency and Royal College of Radiologist's published guidance on the communication of critical, urgent, and unexpected significant radiological findings. Materials and methods: A questionnaire was sent to all UK radiology department audit leads asking for details of their current departmental policy regarding the issuing of alerts; use of automated electronic alert systems; methods of notification of clinicians of critical, urgent, and unexpected significant radiological findings; monitoring of results receipt; and examples of the more common types of serious pathologies for which alerts were issued. Results: One hundred and fifty-four of 229 departments (67%) responded. Eighty-eight percent indicated that they had a policy in place for the communication of critical, urgent, and unexpected significant radiological findings. Only 34% had an automated electronic alert system in place and only 17% had a facility for service-wide electronic tracking of radiology reports. In only 11 departments with an electronic acknowledgement system was someone regularly monitoring the read rate. Conclusion: There is wide variation in practice across the UK with regard to the communication and monitoring of reports with many departments/trusts not fully compliant with published UK guidance. Despite the widespread use of electronic systems, only a minority of departments/trusts have and use electronic tracking to ensure reports have been read and acted upon. Highlights: UK wide audit of communication of significant radiology results. 88% of departments have a communication policy in place. 34% of departments have an automated electronic alert system. 17% of Trusts have facility for service wide electronic tracking of radiology reports.